Life beyond Death: Regulating Posthumous Reproduction in New Zealand - Peart, Nicola (Victoria University of Wellington Law Review, 2015)
This article argues that the current legal regulation of posthumous reproduction in New Zealand is deficient. Posthumous reproduction raises issues in relation to consent, the welfare and status of the child, and even such practical issues as succession rights and estate administration. Drawing on Australian and English case law and legislation, this article proposes reform of the current legal regulation to clarify the consent requirements for collection and use of gametes after the death of the gamete provider, and to address the legal status and associated rights of posthumously conceived children.